2021
DOI: 10.1111/biom.13562
|View full text |Cite
|
Sign up to set email alerts
|

Interim monitoring in sequential multiple assignment randomized trials

Abstract: A sequential multiple assignment randomized trial (SMART) facilitates the comparison of multiple adaptive treatment strategies (ATSs) simultaneously. Previous studies have established a framework to test the homogeneity of multiple ATSs by a global Wald test through inverse probability weighting. SMARTs are generally lengthier than classical clinical trials due to the sequential nature of treatment randomization in multiple stages. Thus, it would be beneficial to add interim analyses allowing for an early stop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(9 citation statements)
references
References 37 publications
0
9
0
Order By: Relevance
“…where 𝐿 𝑘 (𝐱 𝑘 ) is an arbitrary function of 𝐱 𝑘 and we define ∏ 0 𝑣=1 𝜋 𝑣 (𝐴 𝑣,𝑖 , 𝐇 𝑣,𝑖 ; θ𝑣,𝑁 ) = 1. Setting 𝐿 𝑘 (𝐱 𝑘 ) ≡ 0 yields the IPWE that forms the basis for the approach of Wu et al (2021); the IPWE uses only the observed outcomes and no covariate information. It can be an inefficient estimator for 𝑉(𝐝) when there are covariates that are correlated with the outcome.…”
Section: Aipwe For Complete Datamentioning
confidence: 99%
See 4 more Smart Citations
“…where 𝐿 𝑘 (𝐱 𝑘 ) is an arbitrary function of 𝐱 𝑘 and we define ∏ 0 𝑣=1 𝜋 𝑣 (𝐴 𝑣,𝑖 , 𝐇 𝑣,𝑖 ; θ𝑣,𝑁 ) = 1. Setting 𝐿 𝑘 (𝐱 𝑘 ) ≡ 0 yields the IPWE that forms the basis for the approach of Wu et al (2021); the IPWE uses only the observed outcomes and no covariate information. It can be an inefficient estimator for 𝑉(𝐝) when there are covariates that are correlated with the outcome.…”
Section: Aipwe For Complete Datamentioning
confidence: 99%
“…This formulation can be adapted to any set of hypotheses involving functions of the values of regimes of interest. For example, testing the homogeneity hypothesis (1) would involve calculation of chi-square test statistics based on the distributions of (𝑡 𝑠 ), 𝑠 = 1, 2, analogous to Wu et al (2021), which would be compared to corresponding stopping boundaries.…”
Section: Hypothesis Testingmentioning
confidence: 99%
See 3 more Smart Citations